1980
DOI: 10.1007/bf00236149
|View full text |Cite
|
Sign up to set email alerts
|

The vestibulothalamic projections in the cat studied by retrograde axonal transport of horseradish peroxidase

Abstract: Horseradish peroxidase (HRP) was injected or iontophoretically ejected in various thalamic nuclei in 63 adult cats. In 11 other animals HRP was deposited outside the thalamic territory. The number and distribution of labelled cells within the vestibular nuclear complex (VC) were mapped in each case. To a varying degree all subgroups of VC appear to contribute to the vestibulothalamic projections. Such fibres are distributed to several thalamic areas. From the present investigation it appears that generally spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 41 publications
7
46
1
Order By: Relevance
“…The ventral posterior lateral nucleus (VPL) and the nucleus ventralis intermedius (Vim, a transitional zone between the VPL and the ventrolateral thalamic nuclei, see Shiroyama et al, 1999) receive vestibular inputs (Blum et al, 1979b;Blum and Gilman, 1979;Büttner and Henn, 1976;Deecke et al, 1977;Kotchabhakdi et al, 1980;Lang et al, 1979;Magnin and Fuchs, 1977;McCrea, 2008a, 2008b;Matsuo et al, 1994Matsuo et al, , 1995Matsuo et al, , 1999Meng et al, 2007;Nagata, 1986;Sans et al, 1970;Shiroyama et al, 1999) (Fig. 1A-B).…”
Section: Vestibular Projections To the Ventroposterior Complexmentioning
confidence: 99%
See 3 more Smart Citations
“…The ventral posterior lateral nucleus (VPL) and the nucleus ventralis intermedius (Vim, a transitional zone between the VPL and the ventrolateral thalamic nuclei, see Shiroyama et al, 1999) receive vestibular inputs (Blum et al, 1979b;Blum and Gilman, 1979;Büttner and Henn, 1976;Deecke et al, 1977;Kotchabhakdi et al, 1980;Lang et al, 1979;Magnin and Fuchs, 1977;McCrea, 2008a, 2008b;Matsuo et al, 1994Matsuo et al, , 1995Matsuo et al, , 1999Meng et al, 2007;Nagata, 1986;Sans et al, 1970;Shiroyama et al, 1999) (Fig. 1A-B).…”
Section: Vestibular Projections To the Ventroposterior Complexmentioning
confidence: 99%
“…Anatomical studies revealed vestibular projections to the ventroanterior thalamic nucleus (VA) and mostly to the ventrolateral thalamic nucleus (VL) [VA-VL complex] in the cat (Condé and Condé, 1978;Kotchabhakdi et al, 1980;Maciewicz et al, 1982;Nakano et al, 1985;Raymond et al, 1974Raymond et al, , 1976Sans et al, 1970), rat (Nagata, 1986;Shiroyama et al, 1999) and macaque monkey (Lang et al, 1979). Studies conducted in the cat and in the rat showed that the VA-VL complex receives vestibular afferents from the MVN and SVN via the medial longitudinal fasciculus, the ascending tract of Deiters and the superior cerebellar peduncle (Kotchabhakdi et al, 1980;Maciewicz et al, 1982;Nagata, 1986;Nakano et al, 1985;Shiroyama et al, 1999).…”
Section: Vestibular Projections To the Ventroanterior And Ventrolatermentioning
confidence: 99%
See 2 more Smart Citations
“…Widespread, bilateral thalamic projections from the vestibular nuclei (VN) have been reported in the rat (Nagata, 1986;Shiroyama et al, 1995Shiroyama et al, , 1999 and cat (Kotchabhakdi et al, 1980;Maciewicz et al, 1982;Nakano et al, 1985). However, the projection in primates appears to be more discrete.…”
Section: Introductionmentioning
confidence: 99%